2021
DOI: 10.3390/ijms22041677
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts as Complementary Model Systems for the Study of the Pathological Repercussions of Enhanced Synphilin-1 Glycation and Oxidation

Abstract: Synphilin-1 has previously been identified as an interaction partner of α-Synuclein (αSyn), a primary constituent of neurodegenerative disease-linked Lewy bodies. In this study, the repercussions of a disrupted glyoxalase system and aldose reductase function on Synphilin-1 inclusion formation characteristics and cell growth were investigated. To this end, either fluorescent dsRed-tagged or non-tagged human SNCAIP, which encodes the Synphilin-1 protein, was expressed in Saccharomyces cerevisiae and Schizosaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In another study, Seynnaeve et al [18] showed the relevance of yeasts, especially S. cerevisiae, as a model to unravel mechanisms contributing to Synphilin-1-dependent pathology in the context of neurodegenerative diseases, such as Parkinson's disease and Lewy body dementia. They focused on understanding the influence of sugar metabolism disturbances promoting the glycation of proteins on the aggregation of Synphilin-1, which is a partner of α-Synuclein, a primary constituent of Lewy bodies.…”
mentioning
confidence: 99%
“…In another study, Seynnaeve et al [18] showed the relevance of yeasts, especially S. cerevisiae, as a model to unravel mechanisms contributing to Synphilin-1-dependent pathology in the context of neurodegenerative diseases, such as Parkinson's disease and Lewy body dementia. They focused on understanding the influence of sugar metabolism disturbances promoting the glycation of proteins on the aggregation of Synphilin-1, which is a partner of α-Synuclein, a primary constituent of Lewy bodies.…”
mentioning
confidence: 99%